Component-based building instructions for block assembly. Issue 3 (16th April 2017) - Zhang, Man; Igarashi, Yuki; Kanamori, Yoshihiro; Mitani, Jun
Abstract : A LEGO sculpture with fragile constructions of blocks might easily fall to pieces during assembly, making a well-designed set of instructions crucial. A simple layer-by-layer, bottom-up assembly does not work well, especially when over-hanging regions exist. We propose a method for generating component-based building instructions aiming at supporting users to assemble fragile block models efficiently. Our method contains two independent segmentations: segmentation at weakly-connected blocks and segmentation for avoiding floating blocks . Based on these segmentations, the whole model is divided into components. A set of building instructions is generated by deciding the assembly order of the components. The effectiveness of our method is demonstrated through a user study. GRAPHICAL ABSTRACT: